Modified intermixed iteration for solving the split general system of variational inequality problems and applications - Saechou, Kanyanee; Kangtunyakarn, Atid (Computational & applied mathematics, 2021)
Inspired by the works of Siriyan and Kangtunyakarn ( 2018 ) and Yao et al. ( 2015 ), we first introduce the two-step intermixed iteration for finding a common element of the set of the solutions of the split general system of variational inequality problem (SGSV), and also, we prove strong convergence theorem of the intermixed algorithm. Using our main theorem, we prove strong convergence theorems for finding solutions to the split variational inequality problem (SVIP), the split feasibility problem (SFP), and the split common fixed point problem (SCFP). Moreover, we give three numerical examples of these classical problems introduced by the previous studies and an example that conflicts with our main theorem where some conditions fail.